Relationship between autophagy and NLRP3 inflammasome during articular cartilage degradation in oestrogen-deficient rats with streptozotocin-induced diabetes - Florencio-Silva, Rinaldo; Sasso, Gisela Rodrigues da Silva; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP]; Gil, Cristiane Damas; de Jesus Simões, Manuel (Elsevier, 2025)
Background: Estrogen deficiency and Diabetes mellitus (DM) cause joint tissue deterioration, although the mechanisms are uncertain. This study evaluated the immunoexpression of autophagy and NLRP3-inflammasome markers, in rat articular cartilage with estrogen deficiency and DM. Methods: Twenty rats were sham-operated (SHAM) or ovariectomized (OVX) and equally allocated into four groups: SHAM and OVX groups administered with vehicle solution; SHAM and OVX groups treated with 60 mg/kg/body weight of streptozotocin, intraperitoneally, to induce DM (SHAM-DM and OVX-DM groups). After seven weeks, the rats were euthanized, and their joint knees were processed for paraffin embedding. Sections were stained with haematoxylin-eosin, toluidine blue, safranin-O/fast-green or subjected to picrosirius-red-polarisation method; immunohistochemistry to detect beclin-1 and microtubule-associated protein 1B-light chain 3 (autophagy markers), NLRP3 and interleukin-1β (IL-1β) (inflammasome activation markers), along with matrix metalloproteinase-9 (MMP-9), Nuclear factor-kappa B (NFκB), and Vascular endothelial growth factor A (VEGF-A) were performed. Results: Deterioration of articular cartilage and subchondral bone were greater in SHAM-DM and OVX-DM groups. Higher percentages of immunolabeled chondrocytes to NLRP3, IL-1β, MMP-9, NFκB, and VEGF-A, as well as lower percentages of chondrocytes immunolabeled to autophagy markers, were noticed in estrogen-deficient and diabetic groups. These differences were greater in the OVX-DM group. Percentages of immunolabeled chondrocytes showed negative correlation between autophagy markers v.s IL-1β, NLRP-3, MMP-9, NFκB, and VEGF-A, along with positive correlation between VEGF-A vs. MMP-9, NFκB, IL-1β, and NLRP3, and MMP-9 vs. NFκB. Conclusions: In conclusion, autophagy reduction and NLRP3 inflammasome activation in chondrocytes may be implicated in articular cartilage degradation, under estrogen-deficient and DM conditions. Moreover, the combination of estrogen deficiency and DM may potentiate those effects.
Keywords: Articular cartilage; Autophagy; Diabetes mellitus; Estrogen deficiency; NLRP3-inflammasome